The quality assurance of teaching and learning in higher education in South Africa : an analysis of national policy development and stakeholder response - Luckett, Kathleen Margaret (Stellenbosch : University of Stellenbosch, 2006)
The context of this study is the introduction of a new national quality assurance system for South African higher education by an agency of the Department of Education. The purpose of the study is to conduct a critical policy analysis of the Council of Higher Education’s Higher Education Quality Committee’s policy formulation process. In doing so, the study seeks to understand how the quality of teaching and learning practice might be enhanced through quality assurance. In order to answer this question the study examines the literature on quality assurance in higher education and proposes a simple conceptual framework for mapping different approaches to quality assurance. The framework is based on a normative judgment that communicative action is more likely to result in the improvement of teaching and learning practice than instrumental action. Approaches to policy analysis and evaluation research are explored and it is argued that policymaking is a complex multi-faceted process requiring a pluralist research design. This is attempted in the study where a range of research methods are employed from within a critical social science paradigm. The study analyses data gathered at each of the policy stages: setting the policy agenda, policy formulation, policy adoption and policy reformulation, but stops short of researching policy implementation in any depth. The study is therefore classified as a formative, clarificatory evaluation. It seeks to evaluate the conceptualization and design of instruments for quality assurance, stakeholder contribution to policy development and stakeholder response to policy proposals. In particular the study seeks to uncover the different values, discourses and ideologies that stakeholders subscribe to in the policymaking process. The findings of the study show that the HEQC did attempt to work communicatively and consultatively with the higher education community and that it was, in part, due to its consultative efforts, that the final policy instruments were greatly improved. But the study also shows that the consultative process was only partially successful, with serious differences still existing between the HEQC and some stakeholder groups. Different stakeholder approaches to quality assurance are traced to deeper historical, cultural and ideological differences. The study suggests that these factors are likely to hinder the smooth implementation of the HEQC’s policies. The findings of the study also suggest that the challenge of designing a model of quality assurance that caters adequately for both the improvement and accountability purposes of quality assurance was not entirely met in this policymaking process. Furthermore, the study suggests that because the HEQC’s policies were, from the outset, conceived of as a means of furthering the state’s transformation agenda, its idea of quality and its quality assurance procedures are beginning to work ideologically. This has the effect of politicizing the implementation process and undermining the HEQC’s efforts to improve the quality of teaching and learning practice in South African higher education.